Newborn Hearing Screening In The Special Care Nursery Of Hospital Universiti Sains Malaysia Kota Bharu - Al-khamesy, Khaled Saad (2002)
Neonatal hearing loss is a common health problem. Early detection, identification and nanagement prevent the development of hearing loss and its consequences such as delay in speech and language development.